Disorder influenced absorption line shapes of a chromophore coupled to two-level systems - Shenai, Prathamesh M. (2014)
We have carried out a theoretical and numerical study of disorder-induced changes in the absorption line shape of a chromophore embedded in a host matrix. The stochastic sudden jump model is employed wherein the host matrix molecules are treated as noninteracting two-level systems (TLSs) occupying points on a three-dimensional lattice with randomly oriented dipole moments. By systematically controlling the degree of positional disorder (α) attributed to them, a perfectly crystalline (α = 0) or a glassy environment (α = 1) or a combination of the two is obtained. The interaction between the chromophore and the TLSs is assumed to be of the dipole–dipole form. With an increase in α, the broadening of the absorption line shape was found to follow a power-law behavior. More importantly, it is revealed in the long-time limit that the resultant line shape is Gaussian in the absence of disorder but transforms to Lorentzian for a completely disordered environment. For an arbitrarily intermediate value of α, the resultant line shape can be approximately fitted by a linear combination of Gaussian and Lorentzian components. The Lorentzian profile for the disordered medium is attributed to the chomophore–TLS pairs with vanishingly small separation between them.